Interrogating the Spatiotemporal Landscape of Neuromodulatory GPCR Signaling by Real-Time Imaging of cAMP in Intact Neurons and Circuits - Brian S. Muntean; Stefano Zucca; Courtney MacMullen; Maria Dao; Caitlin Johnston; Hideki Iwamoto; Randy Blakely; Ronald L. Davis; Kirill A. Martemyanov (2018)
Modulation of neuronal circuits is key to information processing in the brain. The majority of neuromodulators exert their effects by activating G-protein-coupled receptors (GPCRs) that control the production of second messengers directly impacting cellular physiology. How numerous GPCRs integrate neuromodulatory inputs while accommodating diversity of incoming signals is poorly understood. In this study, we develop an in vivo tool and analytical suite for analyzing GPCR responses by monitoring the dynamics of a key second messenger, cyclic AMP (cAMP), with excellent quantitative and spatiotemporal resolution in various neurons. Using this imaging approach in combination with CRISPR/Cas9 editing and optogenetics, we interrogate neuromodulatory mechanisms of defined populations of neurons in an intact mesolimbic reward circuit and describe how individual inputs generate discrete second-messenger signatures in a cell- and receptor-specific fashion. This offers a resource for studying native neuronal GPCR signaling in real time.